The Effect of Cost of Goods Sold and Sales on Net Income in Food and Beverage Companies Listed on the Indonesia Sharia Stock Index (ISSI) - Silvi Mardhatillah; Sucipto; Ferri Saputra Tanjung (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Profitability in food and beverage companies depends substantially on their ability to increase sales while efficiently controlling the cost of goods sold. However, empirical evidence regarding these relationships among companies listed in the Indonesia Sharia Stock Index remains limited. This study examines the partial and simultaneous effects of the cost of goods sold and sales on net income. A quantitative causal design was employed using data from 33 food and beverage companies selected through purposive sampling, generating 165 firm-year observations for the 2020–2024 period. Secondary data were obtained from annual financial statements published on the official Indonesia Stock Exchange website and analyzed using fixed-effects panel data regression with EViews 12. The results indicate that the cost of goods sold has a negative and significant effect on net income, whereas sales have a positive and significant effect. Simultaneously, both variables significantly affect net income. The adjusted R² value of 0.928343 demonstrates that the model explains 92.83% of the variation in net income. These findings confirm that sales growth must be accompanied by effective cost management to improve corporate profitability. This study contributes empirical evidence on the determinants of net income among Sharia-compliant food and beverage companies in Indonesia and highlights the importance of strengthening production efficiency, inventory control, pricing strategies, and profitable market expansion.